Work–rest pattern, alertness and performance assessment among naval personnel deployed at sea: A cross sectional study - Jaipurkar, Raksha (Med J Armed Forces India, 2019)
BACKGROUND: The combat naval vessels require continuous operational preparedness for guarding the vast coastline. Sailors onboard these ships are at risk for sleep deprivation. Sailors may be vulnerable to chronic fatigue; and decreased performance, vigilance, and cognitive functioning owing to sleep debt, which may affect safety during tactical operations and while transportation of ships. In this study we assessed the work-rest pattern and level of alertness during sailing and non sailing days. METHODS: Thirty-two male participants maintained a 24-h sleep and activity log for 5 days. Furthermore, qualitative gross motor activity was recorded using an actiwatch during these 5 days. Participants also completed four test sessions of personal digital assistant (PDA) based psychomotor vigilance task (PVT) test: pre-sleep, post-sleep, pre-work, and post-work. A comparison of data was performed using the Wilcoxon signed-rank test. RESULTS: Sailors received approximately 1 h less of rest while sailing. There was a significant difference in bedtime, wake-up time, total sleep time, sleep onset latency (SOL), wake up after sleep onset (WASO), and the number of awakenings during the non-sailing and the sailing days. PVT data showed significantly higher reaction times during the sailing days on pre-work and post-sleep sessions. CONCLUSION: Our study shows that although the sailors are not getting sufficient restorative sleep while sailing as compared to non-sailing days, this is not affecting their cognitive functioning while working.